2021
DOI: 10.1108/sasbe-09-2020-0132
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to sustainable construction project management: the case of Iran

Abstract: PurposeThe barriers to integrating sustainable practices into construction project management require extensive resource allocations to resolve. Within developing countries such as Iran (where resources are scarce), remedial strategies adopted must prioritise tackling those barriers that can be expected to yield maximum return on investment. The candidate barriers are many, and this paper aims to identify a hierarchy of barriers, providing a priority list of remedial targets.Design/methodology/approachA mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 76 publications
1
25
1
Order By: Relevance
“…(Alqadami et al, 2020) said that, in the future, the economy would have a higher chance of sustaining itself, and society would be able to create more sustainable living options. For (Fathalizadeh et al, 2021), ensuring that present demand is met while maintaining future generations' possibilities and without harming the environment is crucial to every activity undertaken. There must be a balance between preserving today's resources and ensuring their availability for future generations.…”
Section: Literature Review Sustainability Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…(Alqadami et al, 2020) said that, in the future, the economy would have a higher chance of sustaining itself, and society would be able to create more sustainable living options. For (Fathalizadeh et al, 2021), ensuring that present demand is met while maintaining future generations' possibilities and without harming the environment is crucial to every activity undertaken. There must be a balance between preserving today's resources and ensuring their availability for future generations.…”
Section: Literature Review Sustainability Conceptmentioning
confidence: 99%
“…Otherwise, it might be dangerous and should not be implemented until relevant research is completed. Even though (Fathalizadeh et al, 2021) emphasized the importance of sustainability, they did not consider the real-world issues that may arise when implementing their ideas.…”
Section: Literature Review Sustainability Conceptmentioning
confidence: 99%
“…The complexity of stakeholders' interactions and the shortage of governmental supports prevent contractors from innovating traditional methods characterized by low utilization efficiency and high resource consumption (Mok et al, 2018;Darko et al, 2017). Besides, contractors are often criticized for the limited knowledge and awareness of construction guidelines (Makul, 2020), practice standards (Fathalizadeh et al, 2021) and sustainable technologies (Hwang et al, 2018), which are crucial to the sustainability performance of the construction process. Furthermore, recent studies have found that contractors will undertake unsustainable construction if their competitors use less environmentally friendly materials (Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017). Besides, contractors are often criticized for the limited knowledge and awareness of construction guidelines (Makul, 2020), practice standards (Fathalizadeh et al. , 2021) and sustainable technologies (Hwang et al.…”
Section: Introductionmentioning
confidence: 99%
“…reputation for being wasteful, unsustainable and a major pollutant (Brandão et al, 2021), accompanied by unsatisfactory outcomes for project participants and wider society alike (Newman et al, 2020;Nikmehr et al, 2021). Construction productivity, in contrast to other sectors, has not grown over the last 30 years (Teicholz, 2013;Fathalizadeh et al, 2021). Moreover, poor data management and information exchange inflate project delivery costs by an unnecessary 10-15% (Allen Consulting Group, 2010) while global headlines ubiquitously berate the industry for its poor and unabated safety and quality record (Alizadehsalehi and Yitmen, 2021;Ghodoosi et al, 2021).…”
mentioning
confidence: 99%